The Correlation between Personal Hygiene of Greengrocer and Coliform Bacteria Contamination in Lettuce in Jember Traditional Markets - Qintar Layallia Faza; Diana Chusna Mufida; Muhammad Ali Shodikin; Bagus Hermansyah; Elvia Rahmi Marga Putri (Faculty of Medicine, University of Jember, 2022)
Lettuce is a vegetable that is usually consumed in raw condition or unprocessed by people. Unprocessed vegetables can cause food-borne diseases. Lettuce that is not processed and being consumed directly can cause contamination by Coliform bacteria. The purpose of this study is to know the correlation between Greengrocer’s personal hygiene and Coliform bacteria contamination in lettuce in Jembertraditional markets. This research used a descriptive observational design with the cross-sectional approach. It took place in eight traditional markets in Jember Regency and Microbiology Laboratory, Faculty of Medicine, University of Jember. The samples used were 41 lettuces purchased from 41 traditional market sellers. The microbiological examination was performed in the laboratory using the most probable number method. The results showed that lettuce sellers had bad personal hygiene (92,7%) and the data from the most probable number test found 97,6% contaminated by Coliform bacteria. The bivariate analysis was used to know the relationship between personal hygiene vegetable seller and contamination Coliform bacteria in lettuce. Thep-value was 0,072, which means there was no relationship between personal hygiene vegetable seller and contamination Coliform bacteria in lettuce. Keywords: lettuce, Coliform, contamination, personal hygiene